The Judicial System in the Digital Age: Revisiting the Relationship between Privacy and Accessibility in the Cyber Context - Eltis, Karen (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
Despite technology’s reach into all parts of social life, its effects on the judiciary have been under-theorized. The “Digital Age”, and unfettered usage and access to digital information, will have untold effects on core values of judicial independence, impartiality and the delicate balance between privacy and the “open court” principle. Technology—as well as the dramatically increased availability of information of all kinds and quality—is distorting the judicial process and its outcomes. It is of primary importance, therefore, to identify the broad issues that emerge from the growing use of technology, and to provide a theoretical basis for adjudicating the ongoing tension between privacy and transparency in the judicial setting. Too often the judiciary pits privacy against the “open court” principle and accepts a culturally narrow view of what constitutes privacy and how it affects the judicial process. In particular, this article investigates the effects of online court documents to establish why, despite the current preference for openness and transparency, a contextualized understanding of privacy is desirable. Indeed, if we rethink privacy within the cyber context, it can be considered an ally of openness in the court system.